2019
DOI: 10.1109/access.2019.2919105
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Assessment and Optimization for Urban Rail Transit Networks: A Case Study of Beijing Subway Network

Abstract: With the rapid development of urban rail transit, huge subway systems have been built, which is the best choice for people due to the efficiency, safety, and punctuality. Therefore, the ability of subway systems to resist failures especially interruptions has attracted the attention of operators. In the paper, based on the graph theory, a resilience assessment method is proposed to quantitatively measure the performance and recovery rapidity within unifying metrics and models. We represent the subway network w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Domestic scholars introduced the theory of resilience to China in the 1980s; combined with the requirements of urban sustainable development targets and according to the characteristics of China’s regional development, a large number of empirical studies were then conducted that addressed urban resilience. Li et al studied the development of China’s infrastructure resilience, ecological resilience, and urban resilience in a cross section at a single point in time from the perspectives of the whole country, urban clusters, and provinces (Li et al 2019 ). Huck et al ( 2020 ) examined network construction from the perspective of networks and quantitatively evaluated the urban network resilience of urban agglomerations in the middle reaches of the Yangtze River with the help of complex network theory and the Gephi evaluation structure model (Bostick et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic scholars introduced the theory of resilience to China in the 1980s; combined with the requirements of urban sustainable development targets and according to the characteristics of China’s regional development, a large number of empirical studies were then conducted that addressed urban resilience. Li et al studied the development of China’s infrastructure resilience, ecological resilience, and urban resilience in a cross section at a single point in time from the perspectives of the whole country, urban clusters, and provinces (Li et al 2019 ). Huck et al ( 2020 ) examined network construction from the perspective of networks and quantitatively evaluated the urban network resilience of urban agglomerations in the middle reaches of the Yangtze River with the help of complex network theory and the Gephi evaluation structure model (Bostick et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few scholars have explored urban ecological resilience from the perspective of time and space evolution [29,30]. Some scholars have also quantitatively evaluated and explored the resilience of urban infrastructure from green infrastructure, water supply systems, drainage systems and transportation track networks [31,32]. At the same time, many studies have reported on the connotation and characteristics of urban resilience from the aspects of physical, social and informational three-dimensional systems [33].…”
Section: Introductionmentioning
confidence: 99%
“…The SON has been standardized and applied as a fundamental feature in Fourth Generation (4G) and Fifth Generation (5G) mobile technologies [7, [35][36][37][38]. This feature was introduced by the 3GPP initially in LTE (Release 9 (Rel.9)).…”
Section: Research Overview and Motivationmentioning
confidence: 99%